Cognitive and psychiatric symptoms in genetically determined Parkinson's disease: a systematic review. (28th November 2019) - Piredda, R.; Desmarais, P.; Masellis, M.; Gasca‐Salas, C.
Abstract : The aim was to review the existing reports on cognitive and behavioural symptoms in monogenic forms of Parkinson's disease (PD) and to identify recurring patterns of clinical manifestations in those with specific mutations. A systematic literature search was conducted to retrieve observational studies of monogenic PD. Data pertaining to cognitive and psychiatric manifestations were extracted using standardized templates. The PRISMA guidelines were followed. Of the 1889 citations retrieved, 95 studies on PD‐related gene mutations were included: 35 in SNCA, 35 in LRRK2, four in VPS35, 10 in Parkin, three in DJ1 and eight in PINK1 . Nineteen studies (20%) provided adequate data from comprehensive cognitive assessment and 31 studies (32.6%) outlined psychiatric manifestations through the use of neuropsychiatric scales. Cognitive impairment was reported in all monogenic PD forms with variable rates (58.8% PINK1, 53.9% SNCA, 50% DJ1, 29.2% VPS35, 15.7% LRRK2 and 7.4% Parkin ). In this regard, executive functions and attention were the domains most affected. With respect to psychiatric symptoms, depression was the most frequent symptom, occurring in 37.5% of PINK1 cases and 41.7% of VPS35 and LRRK2 cases. Co‐occurrence of cognitive decline with visual hallucinations was evidenced. Widespread accumulation of Lewy bodies, distinctive of SNCA, PINK1 and DJ1 mutations, results in higher rates of cognitive impairment. Similarly, a higher degree of visual hallucinations is observed in SNCA mutations, probably owing to the more widespread accumulation. The lower rates of α‐synuclein pathology in LRRK2 and Parkin may underpin the more benign disease course in these patients.